Minimally invasive interventions for intracranial pathologies using tubular retractors in the pediatric population: Safety, efficacy, technical aspects and outcomes - Marian Michael Bercu; Andres F. Restrepo-Orozco; Leonard H. Verhey; Casey J. Madura; Anthony M. Avellino; Joseph A. Petronio; Paul A. Mazaris; Justin A. Singer (PLoS ONE, 2025)
Background Minimally invasive surgeries for intracranial pathologies are gaining popularity, recognizing the intrinsic benefits, mostly related to recovery time, while minimizing injury to healthy parenchyma and adjacent functional areas, especially during the resection of deep and centrally located lesions. These procedures require technical familiarity and cultivated surgical experience, coupled with dedicated instruments, appropriate planning, and a stringent patient selection. Objective To describe our novel experience with minimally invasive trans-sulcal parafascicular surgery (MIPS) in a single-center pediatric population, emphasizing the interdependencies between surgical experience, best practices, preparation, and positive surgical outcomes. Methods This single center retrospective review included an electronic medical record (EMR) retrieval of all pediatric patients undergoing minimally invasive trans-sulcal parafascicular surgeries (MIPS) between 2018 and 2023. Clinical, demographic, and radiographic data were captured as were previous surgical procedures, operative approach and technique, operative duration, post-operative day discharge (POD) and length of follow up. Outcomes, including complications and the need for additional interventions, are reported. Results A total of 27 consecutive procedures, treating 22 patients aged 10-months to 19-years were evaluated. Treated pathologies included tumors, vascular lesions, infections, hemorrhage, and hydrocephalus, with the average follow-up > 19 months. Surgical outcomes were similar, if not superior to, the standard of care, considering the extent of resection of various types of lesions, evacuation of hematoma or abscess, as well as complex fenestrations. MIPS procedures were successfully used in a subgroup of patients previously undergoing operations with “standard” approaches. No patients experienced direct complications as a result of the procedure. Recovery times were shorter and the procedure itself was better tolerated in comparison to classical interventions. Conclusions This largest reported pediatric series using MIPS for a variety of pathologies, demonstrates the feasibility, safety, and possibly superior outcomes in children. Technical familiarity and development of surgical experience with MIPS is critical to optimal outcomes.